“How Do You Think You Are Going to be a Pastor?”: Vocation and Disability - Conner, Benjamin T. (Theology today, 2020)
This article defamiliarizes the concept of vocation by attending to one individual’s process of discernment and the issues that that experience and reflection upon it raise for theologies of vocation and the institutions that sustain them. Drawing upon insights from persons with disabilities and disability studies, this article (dis)ables vocation.